Eleven seconds into the unknown a history of the Hyper-X program - Peebles, Curtis (American Institute of Aeronautics and Astronautics, 2011)
Eleven Seconds into the Unknown: A History of the Hyper-X Program is a sequel to the author's first book on the X-43A/Hyper-X project, Road to Mach 10: Lessons Learned from the X-43A Flight Research Program.